UTILIZATION OF DIFFERENTIAL TRANSFORMATION METHOD TO NONLINEAR THREE-POINT SINGULAR BOUNDARY VALUE PROBLEMS - Kumar, Jatin; Sunita; Saini, Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the application of the Differential Transformation Method (DTM) to nonlinear three-point singular boundary value problems (SBVPs). The method incorporates "Faa di Bruno's formula," which utilizes "partial normal ring polynomials," to manage the nonlinearity of the equations. The paper presents error analysis results, comparing them with those obtained through other methods such as the reproducing kernel Hilbert space method (RKHSM). Numerical examples demonstrate the efficacy and reliability of the DTM in providing accurate solutions to these complex problems.